Pengaruh PDRB dan Upah Minimum Provinsi Terhadap Kemiskinan dan IPM di Provinsi-Provinsi Indonesia - Komang Jodi Wiryawan; Ida Ayu Meisthya Pratiwi (Gemawisata: Jurnal Ilmiah Pariwisata, 2024)
Public welfare is the ultimate goal of every economic development. HDI as an indicator of welfare in Indonesia continues to increase from year to year, but is very volatile. The province with the highest HDI points is DKI Jakarta province and the lowest is Papua Province. This shows that the increase has not occurred significantly and there are still disparities in several provinces in Indonesia. This research aims (1) To analyze the direct influence of GRDP and minimum wages on poverty in Indonesian provinces in 2018-2022. (2) To analyze the influence of GRDP, minimum wage and poverty directly on HDI in Indonesian provinces in 2018-2022. (3) To analyze the influence of GRDP and minimum wages on HDI indirectly through poverty in Indonesian provinces in 2018-2022. This research uses secondary data obtained from BPS publications during 2018-2022, with a total of 170 observation points. The data analysis technique used is path analysis with the help of EViews 10 software. The results of the study indicate that PDRB has a significant negative direct effect on poverty, Provincial Minimum Wage has a significant positive direct effect on poverty, both PDRB and Provincial Minimum Wage have a significant positive direct effect on the HDI, and poverty has a significant negative direct effect on the HDI. Poverty is not an intervening variable in the relationship between PDRB and the HDI, but it is an intervening variable in the relationship between Provincial Minimum Wage and the HDI. The implications of this research are that successful economic policies must integrate increases in Gross Regional Domestic Product (GRDP) and Minimum Wage as primary strategies to reduce poverty levels and enhance the Human Development Index (HDI) in Indonesian provinces. Significant increases in GRDP contribute to poverty reduction by evenly distributing economic benefits to disadvantaged groups. Meanwhile, strengthened Minimum Wage policies can elevate worker incomes, bolster purchasing power, and improve access to education and healthcare, thereby potentially boosting HDI. Prioritising poverty reduction is crucial for enhancing overall quality of life, thereby creating better conditions for economic growth and social welfare at the provincial level